Penerapan Metode Moora Dan Simple Additive Weighting Pada Sistem Pendukung Keputusan Penempatan PKL Siswa SMKN 4 Malang - Elsa Apreliani Sutrisno; Anugrah Nur Rahmanto; Hendra Pradibta (Neptunus: Jurnal Ilmu Komputer Dan Teknologi Informasi, 2024)
Placing appropriate Field Work Practices (PKL) for students is very important, because it can maximize the abilities and talents of each student so as to produce graduates who are ready to compete in the world of work. In choosing a place for PKL students at SMK Negeri 4 Malang, the problem that often occurs is a mismatch in students' needs for a PKL place. To overcome this problem, a computer system is needed in the form of a decision support system that can help students at SMK Negeri 4 Malang to choose the right PKL place for students. The decision support system developed in this research uses the Moora and Simple Additive Weighting (SAW) methods in deciding the placement of PKL students. Based on the final results of the decision support system in the form of ranking. Moora's advantages include being stable and strong, this method does not even require an expert in mathematics to use it and requires simple mathematical calculations. Moora also has a good level of selectivity because it can determine goals from conflicting criteria. Where the criteria can be profitable (benefit) or unprofitable (cost). The SAW method was chosen because this method determines the weight value for each attribute, then continues with a ranking process which will select the best alternative. Research is carried out by looking for weight values for each criterion, and then creating a ranking process that will determine the optimal alternative.